DURATION TIME AND EGGS DENSITY TO IMPROVE CLOSED TRANSPORTATION TECHNOLOGY ON EGGS GROUPER - Suko Ismi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
The grouper hatchery technology has been successfully developed and grouper seed can be produced massively and sustainly. Egg is one of key successes in the hatchery processes. Eggs taken from hatchery egg producer were often far away from a final hatchery location. This study tried to find out the effectiveness of eggs transportation duration and densities for eggs’ hatchability of tiger grouper (Epinephelus fuscoguttatus). The first treatment: eggs at a density of 400 000 eggs/8 l sea water, transported with different duration time i.e., 6, 12, 18, and 24 hours. The second treatment: transportation eggs with duration 24-hour at different density i.e., 100,000; 200,000;300,00; and 400,000 eggs/8 l sea waters. Eggs were packaged in a plastic bag with 8 liters of water media, the plastic size 100 cm x 55 cm, ratio water with oxygen was 1: 3, the plastic bag inserted to sterofoam with size 75 cm x 40 cm x 30 cm, to reduce the temperature in sterofoam was added ice the size of 500 grams , wrapped in newspaper, styrofoam covered by selotipe. The results showed that eggs with transportation time of 6 and 12 hours were better and significantly different (P <0.05) than transportation time of 18 and 24 hours. Furthermore, density of 100,000 and 200,000 eggs/8 l sea waters were better and significantly different (P <0.05) than that density of 300,000 and 400,000 eggs/8 l sea waters. Keywords: hatchery, eggs grouper, transportation.